"Via Ethica" in Justifying the Credibility of Christianity and the Church According to Marian Rusecki - Mastej, Jacenty (Verbum Vitae, 2025)
The article presents via ethica in justifying the credibility of Christianity and the Church according to Marian Rusecki (1942–2012). The professor from Lublin, although he was the creator of both the so-called models and an impressive set of credibility arguments, he did not comprehensively develop via ethica. The purpose of the article is to present the basic assumptions of that type of argumentation found in his work. A thorough analysis of his scientific achievements allowed for a critical synthesis and a comprehensive exposition of the methodological conditions of via ethica in Rusecki’s approach. In demonstrating the credibility of Christianity and the Church, within via ethica, the fundamental issue is to define the relationship between religion and ethics. There are many different relations between them and they need each other, therefore, it is a mistake to separate them or to reduce religion only to ethical principles. The foundation of via ethica is the individual existence and dignity of man; these constitute the priority values of religion and ethics. The promotion of the revealed dignity of the human person and the apologia for the human rights that stem from it constitute the credibility of the Christian ethos. The absolutely unique feature of Christianity is the ethos of following Jesus Christ. According to Rusecki, the essence of via ethica is based on the outright uniqueness of Christian ethics. Ethical indications constitute the originality of Christianity in relation to other religions.